DIGITAL LEATNING SPACE AS THE MAIN INNOVATION OF XXI CENTURY - Hulai , Olha; Shemet , Vasylyna; Kabak, Vitalii (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article analyzes the digital educational space as an organization and sequence of activities for the implementation of the educational process. The digital infrastructure, thanks to the interconnected systems and networks of the University and other Internet resources, allows us to constantly introduce new opportunities and maintain suitability for learning in different conditions. The importance of digital competence for improving teaching and learning is noted.